(untitled) (Conference Zone, 2022)
No matter what the world is like, as a society develops in each country, it is natural to see constructive and destructive ideas, uncompromising struggle between them, their positive and negative features. I have to say that these ideas come into being, they evolve, they eventually come to an end. The length of their lives depends on the people who follow them, the period of existence of the forces that drive them, especially the validity, populism, humanity and goodness of these ideas